Comparison of Computer Interface Devices for Persons With Severe Physical Disabilities. - Lau, Cynthia; O'Leary, Stephanie (American Journal of Occupational Therapy, 1993)
This research employed a descriptive case study design to compare subjects' performance using three computer input devices: the Tongue Touch Keypad, the Head-Master, and the mouthstick. The sample consisted of four students with severe physical disabilities enrolled in an adaptive computer class at a community college. Components of perfonnance examined were input speed, accuracy, and level of perceived exertion. Subjects' acceptance of each of the interface devices was also examined. Results showed input speed to be the fastest with the mouthstick, followed by the Head-Master and then the Tongue Touch Keypad. Accuracy of input did not van' significantly. Three subjects rated the Tongue Touch Keypad as requiring the lowest rate of perceived exertion, followed by the HeadMaster and then the mouthstick. Overall perfonnance did not necessarily affect subjects' acceptability ratings of the devices. Information from this study will assist therapists in evaluating the effectiveness and desirability of computer interface devices for patients.